An optimal consumption and investment problem with quadratic utility and subsistence consumption constraints: a dynamic programming approach - Shin, Yong Hyun; Koo, Jung Lim; Roh, Kum Hwan (Mathematical modelling and analysis, 2018)
In this paper, we analyze the optimal consumption and investment problem of an agent who has a quadratic-type utility function and faces a subsistence consumption constraint. We use the dynamic programming method to solve the optimization problem in continuous-time. We further provide the sufficient conditions for the optimization problem to be well-defined.